The Politics of Chaos in the Middle East - Amr G. E. Sabet (International Institute of Islamic Thought, 2009)
This relatively short and succinct book, written by a prominent French political analyst, offers an insight not only into post-9/11 American military and strategic dilemmas, but also a glimpse into the respective European conceptions and ways of thinking. Its main thrust is that the American reaction to the events of that day, far from producing an outcome in the image of a “hyperpower in a unipolar world,” has instead bogged it down as a “power tied up in knots, incapable of policing the world” (p. 3). This “hopeless” situation, according to Roy, was brought on the Americans by themselves, rather than as a result of their enemies, be they the Taliban, al-Qaeda, or Iran (p. 3). While the American invasion of Iraq produced deep geostrategic transformations in the Middle East, these did not always produce the results that American decision makers had countenanced ...